Molecular Mimicry of SecA and Signal Recognition Particle Binding to the Bacterial Ribosome - Lara Knüpffer (American Society for Microbiology, 2019)
ABSTRACT Bacteria execute a variety of protein transport systems for maintaining the proper composition of their different cellular compartments. The SecYEG translocon serves as primary transport channel and is engaged in transporting two different substrate types. Inner membrane proteins are cotranslationally inserted into the membrane after their targeting by the signal recognition particle (SRP). In contrast, secretory proteins are posttranslationally translocated by the ATPase SecA. Recent data indicate that SecA can also bind to ribosomes close to the tunnel exit. We have mapped the interaction of SecA with translating and nontranslating ribosomes and demonstrate that the N terminus and the helical linker domain of SecA bind to an acidic patch on the surface of the ribosomal protein uL23. Intriguingly, both also insert deeply into the ribosomal tunnel to contact the intratunnel loop of uL23, which serves as a nascent chain sensor. This binding pattern is remarkably similar to that of SRP and indicates an identical interaction mode of the two targeting factors with ribosomes. In the presence of a nascent chain, SecA retracts from the tunnel but maintains contact with the surface of uL23. Our data further demonstrate that ribosome and membrane binding of SecA are mutually exclusive, as both events depend on the N terminus of SecA. Our study highlights the enormous plasticity of bacterial protein transport systems and reveals that the discrimination between SRP and SecA substrates is already initiated at the ribosome. IMPORTANCE Bacterial protein transport via the conserved SecYEG translocon is generally classified as either cotranslational, i.e., when transport is coupled to translation, or posttranslational, when translation and transport are separated. We show here that the ATPase SecA, which is considered to bind its substrates posttranslationally, already scans the ribosomal tunnel for potential substrates. In the presence of a nascent chain, SecA retracts from the tunnel but maintains contact with the ribosomal surface. This is remarkably similar to the ribosome-binding mode of the signal recognition particle, which mediates cotranslational transport. Our data reveal a striking plasticity of protein transport pathways, which likely enable bacteria to efficiently recognize and transport a large number of highly different substrates within their short generation time.